Analisis Strategi Pembelajaran Istima’ Dalam Meningkatkan Hubungan Interpersonal - HSB, Ahmad Husein; Ananda, Raditya; Sir, Hariyanti; Maulana, Latif; Sari, Rizka (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2025)
Listening skills (istima’) play a crucial role in mastering Arabic, particularly in fostering effective communication. However, istima’ instruction often emphasizes linguistic aspects without considering its contribution to the development of interpersonal relationships. This study aims to analyze listening learning strategies that enhance students’ interpersonal abilities within the context of Arabic language learning. The method used is descriptive qualitative with a field study approach involving observation, interviews, and documentation at an Islamic senior high school in Riau. The findings reveal that strategies such as conversation simulation, listening to authentic audio, and group discussions encourage students to become active listeners, increase empathy, and foster openness in interaction. The study concludes that communicatively and contextually designed istima’ instruction has a significant impact on strengthening students’ interpersonal relationships.